2010
DOI: 10.1590/s1519-566x2010000400026
|View full text |Cite
|
Sign up to set email alerts
|

Redução da sobrevivência da broca-do-café, Hypothenemus hampei (Ferrari) (Coleoptera: Scolytidae), e do seu ataque aos frutos de café pela pulverização com nim em laboratório

Abstract: -Aqueous solutions of neem oil and aqueous extracts of neem seeds and leaves were sprayed on coffee fruits for laboratory evaluation of their effi ciency in reducing infestation of the coffee borer, Hypothenemus hampei (Ferrari), in multi-choice preference assays in laboratory. Neem oil and extracts reduced infestation of fruits in a dose-dependent manner, acting as a repellent. At 0.5%, 1% and 1.5%, the oil reduced fruit infestation by 30.2%, 42.5% (P > 0.05), and 58.6% (P  0.05), respectively, as compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…However, for the coffee berry borer, only the extract of the green leaves of castor oil plants (2.2 g L -1 of boiled water) was evaluated, which reduced the number of individuals per sample, when analysed 72 hours after application (Pérez et al, 2012). For the neem oil (Dalneem ® , 0.1% (v v -1 ) of azadirachtin; Dalneem Brazil), the mortality of and the repellency to H. hampei caused by neem oil resulted in a reduced number of grains damaged by this pest (Depieri & Martinez, 2010). The authors found mortality of H. hampei up to 88.3% when the females and the beans were sprayed with a 1% (v v -1 ) aqueous solution of emulsifiable neem oil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the coffee berry borer, only the extract of the green leaves of castor oil plants (2.2 g L -1 of boiled water) was evaluated, which reduced the number of individuals per sample, when analysed 72 hours after application (Pérez et al, 2012). For the neem oil (Dalneem ® , 0.1% (v v -1 ) of azadirachtin; Dalneem Brazil), the mortality of and the repellency to H. hampei caused by neem oil resulted in a reduced number of grains damaged by this pest (Depieri & Martinez, 2010). The authors found mortality of H. hampei up to 88.3% when the females and the beans were sprayed with a 1% (v v -1 ) aqueous solution of emulsifiable neem oil.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the azadirachtin has an antifeedant effect for a wide range of insects and may cause sterility in female insects (Isman, 2006). The emulsifiable oil, the extracts of leaves and the seeds of neem were repellent to and increased the mortality of the coffee berry borer (Depieri & Martinez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [15] also found positive results for the use of emulsifiable neem oil on coffee fruits in the control of Hypothenemus hampei (Ferrari) (Coleoptera: Scolytidae), known as Coffee-borer.…”
Section: Fig 2 C Ferruginea Individualized In a Petri Dish With A Eucalyptus Seedling Leaf Previously Treated At The Selected Concentratimentioning
confidence: 95%
“…Therefore, the obtained data suggests that the botanical insecticide is able to control H. hampei, compared with the traditionally used pesticides, with proximity between the treatments. Depieri & Martinez (2010) concluded that spraying neem oil on H. hampei insects can lead to death by ingestion associated to repellency caused by contact, resulting in a low incidence of bored fruits. The authors reported an average mortality of 58%, close to that found in the present study, which is indicative that the reduction in insect incidence observed here is probably due to the botanical formulation.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of the used castor oil included: 1.10% palmitic, 4.50% linoleic, 4.02% oleic, 0.50% stearic, and 88.04% ricinoleic fatty acids. Depieri & Martinez (2010) observed how spraying aqueous solutions of neem oil and aqueous extracts of neem seeds and leaves on coffee fruits reduced the attack by H. hampei. The authors concluded that the aqueous seed extract was more promising than neem oil and the leaf extract, but did not evaluate their compositions.…”
Section: Introductionmentioning
confidence: 99%